Modified grey wolf optimisation based reduced device count 17-level hybrid multilevel inverter - Routray, A.; Singh, R.K.; Mahanty, R. (John Wiley and Sons Inc, 2021)
A 17-level hybrid multilevel inverter (HMLI) using modified grey wolf optimisation (MGWO) is proposed here. The proposed HMLI requires only a single dc source and a lesser number of circuit elements to obtain a multilevel voltage level. The proposed HMLI can also enhance the input voltage and has reverse current carrying capability. The selective harmonic elimination pulse width modulation technique is implemented through MGWO for determining the optimal switching angles of the proposed HMLI to eliminate lower order harmonics. The MGWO algorithm gives improved results as compared to other existing optimisation algorithms in terms of fitness value, convergence speed and harmonic profile of the output voltage. The proposed HMLI is also compared with some of the other existing HMLIs in terms of the number of circuit elements, peak inverse voltage and total blocking voltage to exhibit its advantages. Finally, a 550 W prototype is fabricated in the laboratory to evaluate the effectiveness of the proposed HMLI. © 2021 The Authors. IET Power Electronics published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology
Keywords: grey wolf; optimisation; 17-level hybrid multilevel inverter